A comparative study of the complex formation of molybdenum(VI) and tungsten(VI) with ligands derived from carboxlic acids - Rohwer, E. A. (Elisabeth Anna) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2000.